TRENDS IN THE TOP RETAIL TRADE IN ROMANIA - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the retail trade in Romania during the last decade, 2008-2017, pointing out the performance achieved by the top 10 retailers Kaufland, Carrefour, Lidl, Auchan, Mega Image, Profi, Metro, Selgros, Rewe and Cora Hypermarket, based on the number of stores, turnover, net profit, market share and average number of employees. Romanian market proved to be a good business environment for retailers as long as consumption is increasing determined by the growth of wages and reduction of VAT. Both hypermarkets, supermarkets, discount stores and minimarkets have appeared on Romania's map and their number continue to grow as expected in the near future. The number of square meters commercial space per inhabitant is enough high as long as Romanians like shopping. For this reason, the retailers have to develop new strategies to strengthen their business and cover much better consumers' needs. Important efforts should be made to develop the minimarket network in the smaller cities and even in the rural localities, the commercial space should be modernized and offer a pleasant and attractive environment for shopping, e-commerce should be extended as a modern purchasing alternative, the offer should be diversified including more Romanian products as preferred by consumers, organic products should be more visible on the shelves which have to offer healthy products to the clients, a more intensive advertising should be useful for a better information of the consumers and for increasing sales and profit of the retailers.